PKM Pelatihan Penggunaan Aplikasi Laporan Tagihan Internet Pada CV. Megadata Berbasis Bot WhatsApp - Maulidiansyah; Moch Dzikri Hidayatullah; Mohammad Ainul Yaqin Syah; Roji Fayyumi; Zhylal Al Fath (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In this community service project, the primary partner of focus is an internet company. The issue that the partner is facing is related to the inefficient billing of WiFi services to consumers. The form of community service to be carried out is the development of a WhatsApp Bot-based WiFi billing system. This community service aims to develop a WhatsApp Bot-based solution that can enhance billing processes for CV. Megadata's consumers. Therefore, this community service project will involve designing and implementing a WhatsApp Bot-based system that facilitates WiFi billing. By leveraging the popular and user-friendly WhatsApp communication platform, this training will equip WiFi service providers with the skills to implement a billing system that allows customers to make payments, ask questions, and receive notifications more conveniently through WhatsApp. The training will also address integration with existing billing systems, the use of artificial intelligence to manage customer requests, and conducting an analysis of the impact on operational efficiency and customer satisfaction. It is expected that this training will provide WiFi service providers with a strong understanding of how to optimize their billing systems, reduce administrative costs, and enhance the customer experience. This will support their business growth in the ever-evolving digital era by offering innovative and more efficient solutions for managing WiFi services and interacting with customers. In conclusion, this community service project has provided significant benefits to CV. Megadata in enhancing the quality of billing for its consumers. Consequently, CV. Megadata can continue to adapt to technological advancements and sustainably improve consumer satisfaction.